Dynamic linkages and volatility spillover : effects of oil prices on exchange rates, and stock markets of emerging economies - Bagchi, Bhaskar; Dandapat, Dhrubaranjan; Chatterjee, Susmita (Bingley : Emerald Group Publishing Limited, 2016)
This book examines the dynamic relationship and volatility spillovers between crude oil prices, exchange rates and stock markets of emerging economies. Although considerable literature on relationship between exchange rates and stock markets as well as affiliation between oil prices and stock markets is available, unfortunately very little research has been conducted to analyze the volatility spillovers and dynamic relationship between crude oil prices, exchange rates and stock markets of India covering pre-recession, recession and post-recession period. More particularly, a clear research gap has been found in analyzing the volatility spillovers between above three variables in respect of India irrespective of the importance of oil prices and exchange rates as essential parameters for economic recovery and growth of the capital markets. Furthermore, the stock returns volatility is partly explained by volatility in crude oil prices and exchange rates. The volatility in stock markets is partly due to foreign interference that persuades a correlation with international markets through crude oil prices and exchange rates. Hence, a new publication on this topic is needed at this time.
Includes bibliographic references and index.
Print version record
Keywords: Petroleum products -- Prices -- Developing countries; Business & Economics -- International -- Economics; International finance